Exploring the Depths: The Significance of Analysis in Unveiling the Other Side of Perception - Diyah Nurhayati; Windy Esti Andari; Tria Aprilia (International Forum of Researchers and Lecturers, 2024)
This study explores the role of analysis in revealing other sides of perception in the context of works of art, especially in music. With a focus on the theme